The Interdependence of Macroeconomic Stability Parameters: The Case of the Western Balkans - Lojanica, Nemanja (Industrija, 2025)
The primary objective of this paper is to highlight the main types of causality between economic growth, inflation, and unemployment, as well as to reexamine the fundamental regularities associated with these variables. To investigate the potential dependence among the variables, a sample of Western Balkan countries (Albania, North Macedonia, Serbia, Bosnia and Herzegovina) over the period 1995–2024 is used. As the appropriate methodological framework, panel cointegration, the Mean Group (MG) cointegration technique, and panel causality tests were employed. The study established the existence of cointegration among the variables. The key finding concerns the positive and statistically significant impact of inflation on economic growth, as well as the causality running from inflation to economic growth. The results align with the view that a moderate inflation rate in the short term is associated with economic growth, and that stable and sustainable economic growth requires price stability. While the benefits of moderate price increases in the short run can be effective, the focus should remain on the long-term horizon.